Aspectos gramaticais da língua Terena - Gardenia Barbosa Neubaner Nascimento (2012)
The main objective of this dissertation is to present a description of some aspects of Terena grammar. The analysis mainly focuses on grammatical topics like phonology, possession marking, verbal morphology and the status of the agreement affixes. Regarding phonology, the analysis is concerned with the consonant and vowel distribution in order to set the phonemic system of the language. In addition, I deal with how possession is expressed in the language.One of the findings is that Terena employs head-marking and juxtaposition to encode the possession relation between the possessor and the possessed noun.Another conclusion is that the grammar differentiates alienable from inalienable possession. With regard to the verbal morphology, we found that the language can employ several types of valence changing devices. In line with this, it was possible to segment verbal morphemes related to applicative meaning, causative formation, passive voice, reflexive and reciprocal. Finally, based on Jelinek (1989), I launch the proposal that Terena is a pronominal argument language. A piece of evidence in favor of this analysis has to do with the fact that, when the verbal arguments are of first or second person, they are necessarily encoded in theverbal morphology by means of verbal affixes. Interestingly, these affixes are in complementary distribution with the lexical arguments. This fact thus proves that the verbal person affixes in Terena are not agreement, but argument in nature.